Useful apps: a teaching process - learning applied to the daily needs - Jacinto, Adriana da Silva; Marteli, Alice Nardoni; Pires, João Gabriel Dias; Jacinto, Jaqueline da Silva (Universidade Estadual de Campinas, 2018)
The outcome of Education should be efficient, effective and meaningful learning. However, in the 21st century, it is well known that there are many difficulties in teaching and learning. New computational technologies are pointed out as a factor that can bring benefits to the teaching and learning process, since theyshould support new pedagogical strategies. So, the problem lies in how to develop and apply new pedagogical strategies to make student aware about his responsibility for his own teaching-learning process. This article proposes a teaching-learning process that unites the use of smartphones, application programming and critical reasoning about problems that the student sees in his daily life. This process was applied to undergraduate students of the Database Technology course. Among the obtained results, there was the development of a collaborative application to help manage the risks of hydro - meteorological environmental disasters. This app is intended to alert responsible agencies to they can take preventive attitudes to evacuate areas at risk, more quickly than commonly used. This and other results indicate the validity of the proposal.